Effect of mulching and subsurface drip irrigation on soil water status under arid environment - Ahmed A. Al-Othman; Mohamed A. Mattar; Mohammed A. Alsamhan (Spanish Journal of Agricultural Research, 2020)
Aim of study: We investigated water evaporation of the soil surface and the soil water distribution under different mulching techniques using subsurface drip irrigation (SDI) system.